Optimization of Dikmas Then by the Dikyasa Unit in Reducing Traffic Violations at the Karawang Police Jurisdictios - Nyoman Santhi Purwani (Advances in Police Science Research Journal, 2021)
The high number of traffic violations in West Java, especially in the Sat Traffic Police of the Karawang Police. This is due to the lack of socialization about orderly traffic and the lack of knowledge about traffic in the community as a whole. The high number of violations can affect the high accident rate at the Karawang Police, so that the Traffic Unit at the Karawang Police must prioritize education to the community by Optimizing the Dikyasa Unit Then the Karawang Police through Dikmas Then to students in the hope of overcoming traffic problems in Karawang. The research objectives in this thesis are to determine the condition of the Dikyasa Unit personnel in carrying out Dikyasa's tasks, knowing the performance of the Dikyasa Unit, knowing the intensity of Dikmas Lantas activities, and the factors that affect the optimization of Dikmas then in the last 3 (three) years whether it has been successful or not. The research location is in the area of ​​the Karawang Police. This research uses qualitative methods, while the theories and concepts used to analyze this problem are Management Theory, Motivation theory, Competency theory, Optimization concept, Then Kamseltibcar concept, and Dikmas Lantas Concept from the National Police Chief Implementation Guidelines: Juklak / 5 / V / 2003 dated 29 May 2003 concerning Guidelines for Implementing Community Education in the Traffic Sector. Data collection techniques that can be used are interviews, observation, and document study. The results obtained in this study are that the implementation of Dikmas Lantas at the Karawang Police is still not optimal due to the budget and human resources that are still lacking, Kamseltibcar Lantas in Karawang is also still far away because there are still many violations. The Karawang Traffic Police recommends coordinating and collaborating with relevant agencies in covering the shortcomings that exist in the Karawang Traffic Police, providing additional new personnel and holding training / dikjur, there is a need for the latest innovations in the implementation of Dikmas Then so that it is easily conveyed to the whole community to become pioneers of passing safety cross.